Convivência em uma orquestra comunitária: um olhar para os processos educativos - Joly, Maria Carolina Leme (Universidade Federal de São Carlos, 2007)
This work is the result of a research for Masters, which aims to highlighting and analyzing the educational processes present in a community orchestra from the practice of social coexistence of a group of musicians. The Experimental Orchestra of UFSCar (São Carlos Federal University), where the data collection happened is formed by amateur and professional musicians, from different communities, with different degrees of development and musical knowledge. The theoretical reference adopted is based on works of Paulo Freire, Ernani Fiori, Moacir Gadotti, Agnes Heller, Maria Waldenez Oliveira, as well as others related to Social Practice and Educational Processes fields. Concerning Musical Education, works of Viviane Beineke, Teca Brito, Vanda Freire, Marisa Fonterrada, Carlos Kater, Hans Koellreuter, were adopted among others. This study qualifies as qualitative research with participant observation and the data were collected by semi-structure interviews with five orchestra participants. From the analysis of the data it was possible to highlight some musical, human and social living processes which happen through living in diversity such as respect for differences, tolerance, friendship, solidarity and others
Keywords: Educação musical; Práticas sociais e processos educativos; Convivência; Orquestra comunitária; Comunidade; Musical education; Social practices and educations processes; Coexistence; Community orchestra; Community; CIENCIAS HUMANAS::EDUCACAO